Evaluation of [18F]tetrafluoroborate as a Potential PET Imaging Agent in a Sodium Iodide Symporter-Transfected Cell Line A549 and Endogenous NIS-Expressing Cell Lines MKN45 and K1. (27th February 2022) - Niu, Mengda; Qin, Jingjing; Wang, Liang; He, Yujia; Tian, Chuanhuizi; Chen, Yanyan; Huang, Pufeng; Peng, Zhiping
Abstract : [ 18 F]tetrafluoroborate (TFB) has been introduced as the 18 F-labeled PET imaging probe for the human sodium iodide symporter (NIS). Noninvasive NIS imaging using [ 18 F]TFB has received much interest in recent years for evaluating various NIS-expressing tumors. Cancers are a global concern with enormous implications; therefore, improving diagnostic methods for accurate detection of cancer is extremely important. Our aim was to investigate the PET imaging capabilities of [ 18 F]TFB in NIS-transfected lung cell line A549 and endogenous NIS-expressing tumor cells, such as thyroid cancer K1 and gastric cancer MKN45, and broaden its application in the medical field. Western blot and flow cytometry were used to assess the NIS expression level. Radioactivity counts of [ 18 F]TFB, in vitro, in the three tumor cells were substantially higher than those in the KI inhibition group in the uptake experiment. In vivo PET imaging clearly delineated the three tumors based on the specific accumulation of [ 18 F]TFB in a mouse model. Ex vivo biodistribution investigation showed high [ 18 F]TFB absorption in the tumor location, which was consistent with the PET imaging results. These results support the use of NIS-transfected lung cell line A549 and NIS-expressing tumor cells MKN45 and K1, to investigate probing capabilities of [ 18 F]TFB. We also demonstrate, for the first time, the feasibility of [ 18 F]TFB in diagnosing stomach cancer. In conclusion, this study illustrates the promising future of [ 18 F]TFB for tumor diagnosis and NIS reporter imaging.